2017
DOI: 10.1055/s-0037-1608876
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Mortality for Premature and Low Birth Weight Neonates: A Systematic Review

Abstract: The majority of reviewed studies found poorer male mortality outcome. A small number of studies maintained a null association between sex and mortality. This indicates male premature and LBW neonates experience higher risk of mortality by discharge compared with females, an observation which may inform clinical decision making in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 65 publications
2
8
0
1
Order By: Relevance
“…This is supported by previous study findings reported in sub-Saharan Africa [65], Pakistan [66], and Brazil [67]. This could be due to the slower lung maturation among males compared to females that predispose male children to repeated respiratory infections such as pneumonia, bronchiolitis, otitis media, and hyperactive airway disease which could contribute to the increased risk of stunting among males [68]. Children born with multiple births are at higher risk of being stunted compared to singletons.…”
Section: Plos Onesupporting
confidence: 88%
“…This is supported by previous study findings reported in sub-Saharan Africa [65], Pakistan [66], and Brazil [67]. This could be due to the slower lung maturation among males compared to females that predispose male children to repeated respiratory infections such as pneumonia, bronchiolitis, otitis media, and hyperactive airway disease which could contribute to the increased risk of stunting among males [68]. Children born with multiple births are at higher risk of being stunted compared to singletons.…”
Section: Plos Onesupporting
confidence: 88%
“…For example, data from the U.K. Biobank study in over 400,000 adults aged 40–69 years has shown that every three kilogram increment in grip strength was associated with approximately 8% lower mortality 32 . Since approximately 15% of all live births are low birth weight births 33 , which are associated with lifelong health consequences 34,35 , preventing low birth weights, even within the at-term range, may have long-term effects on markers of health such as grip strength. It is of importance to state that not all low preterm or low birth weights can or should be prevented, for example spontaneously occurring births.…”
Section: Discussionmentioning
confidence: 99%
“…En el modelo explicativo, se ingresó como variable de ajuste confusor el sexo del bebé, el cual demostró que en los nacidos vivos de sexo masculino se aumentó de manera significativa el peso al nacer (β: 196,2 IC95 %: 7,5-385,1). Estos resultados son consistentes con los análisis de Duc Vu et al (13), quienes mediante una revisión sistemática concluyeron que los neonatos varones experimentan un mayor peso al nacer. Esta relación fue evidenciada por Meshram et al (14) en población india y por González-Cossío et al (15) en población mexicana.…”
Section: Discussionunclassified